The Canadian Industrial Relations Research Institute

(untitled) (Département des relations industrielles de l'Université Laval, 1964)
On june 6th., 1964 at McGill University, Montreal, was held the first annual meeting of the Canadian Industrial Relations Research Institute.On that occasion, was adopted the constitution of the group and officers were elected. Papers were presented by Father Gérard Dion, Laval University, Quebec, Dr J.T. Montague, British Columbia University, and by Dr Gil Schonning, Department of Labour, Ottawa. The officers elected are the following: President: H.D. Woods (McGill University); Vice-presidents: Father Gerard Dion (Laval University), Bora Laskin (Toronto University); Secretary: Frances Bairstow (McGill University); members: J.T. Montague (British Columbia University), Roy Brookbank (Dalhousie University). The Business Office of the Institute is located at: 3666 McTavish Street, Montreal, Que. Foliowing is the text of the constitution.